2017
DOI: 10.1073/pnas.1617940114
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of pollination services and coffee suitability under climate change

Abstract: Climate change will cause geographic range shifts for pollinators and major crops, with global implications for food security and rural livelihoods. However, little is known about the potential for coupled impacts of climate change on pollinators and crops. Coffee production exemplifies this issue, because large losses in areas suitable for coffee production have been projected due to climate change and because coffee production is dependent on bee pollination. We modeled the potential distributions of coffee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 37 publications
1
47
0
12
Order By: Relevance
“…Another study showed that passion fruit pollinators belonging to the genus Xylocopa could face reductions of up to 90% in their distribution areas in the Brazilian savanna (Giannini et al 2013). A potential reduction of 8-18% in coffee-pollinating bees has been demonstrated for Latin America, affecting up to 30% of the future area of coffee production (Imbach et al 2017). The tomato pollinators will likely face reductions in their areas of occurrence in Brazil, and Bombus morio Swederus 1787 will potentially face the largest reduction (up to 71% in the most pessimistic scenario) (Elias et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that passion fruit pollinators belonging to the genus Xylocopa could face reductions of up to 90% in their distribution areas in the Brazilian savanna (Giannini et al 2013). A potential reduction of 8-18% in coffee-pollinating bees has been demonstrated for Latin America, affecting up to 30% of the future area of coffee production (Imbach et al 2017). The tomato pollinators will likely face reductions in their areas of occurrence in Brazil, and Bombus morio Swederus 1787 will potentially face the largest reduction (up to 71% in the most pessimistic scenario) (Elias et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true of smallholder shade coffee systems characterized by complex and structurally diverse shade management practices [5][6][7]. In contrast to sun-grown coffee (sun coffee) or coffee grown under sparse shade, complex rustic shade coffee agroforests are associated with a diversity of provisioning ecosystem services [6] and a high diversity of associated fauna, including mammals, arthropods, ants, butterflies, and bees [7,8]. Given their structural and biological similarity to forested lands, rustic shade coffee lands also provide habitat connectivity for forest-dependent species navigating fragmented landscapes [9].…”
Section: Introductionmentioning
confidence: 99%
“…For the foreseeable future, coffee will remain “the best part of waking up” and all that follows thereafter in the spectrum of human social activities. That said, climate change forecasts promise little more than hardships for coffee producers [30], due to expansion of the range and prevalence of warm temperature pests such as the coffee borer [31], and Brevipalpus mites, the vector of CoRSV, while having a negative impact on beneficial pollinators critical for high yields [32]. Warmer average temperatures mean that diseases such as coffee rust will be able to reach higher elevations that are traditionally relatively free of this disease, a fact certainly vital to organic coffee producers.…”
Section: Corsv: Its Genome Organization and Occurrencementioning
confidence: 99%